The spider genus Prosoponoides (Araneae: Linyphiidae) in China - Chen, Qianjun; Zhong, Yang; Liu, Jie; Chen, Jian (Zootaxa, 2020)
The species of Prosoponoides Millidge & Russell-Smith, 1992 from China are studied, including one new species, Prosoponoides youyiensis Liu & Chen n. sp., and two known species, Prosoponoides hamatum Millidge & Russell-Smith, 1992 and Prosoponoides sinense (Chen, 1991). Morphological descriptions and illustrations of P. hamatum and P. youyiensis Liu & Chen n. sp. are given, and digital photos of P. sinense are provided.